Chemotherapy Resistance in Remutation of Epidermal Growth Factor Receptor Wild Type Becomes a Positive Type and Back Becomes a Wild Type in A Patient with Lung Adenocarcinoma - Kurniawan, Kristo; Sugiri, Yani Jane; Parsama Putra, Ngakan Putu; Yudhanto, Handy Setyo (Malang Respiratory Journal, 2021)
Introduction: Lung cancer is the most common type of cancer worldwide (11.6%) and the leading cause of death due to cancer throughout the world. One type of lung cancer that is often found is Adenocarcinoma, 35-40%. Mutations in EGFR often occur in patients with pulmonary Adenocarcinoma, especially in Asia. Chemotherapy selection for pulmonary adenocarcinoma patients based on the status of their EGFR mutations. Positive EGFR mutations can get treatment with Tyrosine Kinase Inhibitors. Giving chemotherapy can affect changes in EGFR mutation status. Patients with chemotherapy treatment can experience resistance to chemotherapy either primary or acquired resistance through a variety of mechanisms.Case Description: we reported one case of a 56-year-old man with pulmonary adenocarcinoma who had a positive change in EGFR-type from wild type mutations and then returned to a wild type. Patients were initially diagnosed with wild-type pulmonary adenocarcinoma from EGFR examination of tissue biopsy and given conventional chemotherapy. During the evaluation, progression occurred so that the status of the EGFR mutation was examined using ct-DNA and the result was mutation deletion exon 19 so that the patient obtained Gefitinib. Due to progressive return, the patient again examined EGFR status from tissue biopsy obtained using pleuroscopy and obtained an EGFR wild type. Patients again get conventional chemotherapy.Discussion Changes in the status of EGFR mutation in pulmonary adenocarcinoma patients and chemotherapy resistance can occur in patients with chemotherapy treatment.Â